CD147 and matrix-metalloproteinase-2 expression in metastatic and non-metastatic uveal melanomas. Issue 1 (December 2016) - Lüke, Julia; Vukoja, Vlatka; Brandenbusch, Tim; Nassar, Khaled; Rohrbach, Jens; Grisanti, Salvatore; Lüke, Matthias; Tura, Aysegül
Abstract Background Extracellular matrix remodelling regulated by matrix-metalloproteinase (MMP) inducer (CD147) is a crucial process during tumor cell invasion and regulation of blood supply. In this study, we evaluated the correlation of CD147 and MMP-2 expression with major prognostic factors for uveal melanoma and the development of metastasis. Me thods The expression of CD147 and MMP-2 was analyzed in 49 samples of uveal melanomas. Triple immunofluorescence stainings using markers against glial cells (GFAP), endothelial cells (CD34) and macrophages (CD68) were performed to further analyse the exact localisation of CD147 and MMP-2 positivity. In 28 cases clinical metastatic disease were found. The remaining 21 cases showed no signs of metastatic disease for an average follow-up of 10 years. Correlation analysis (Pearson correlation) was performed to analyse the association of CD147 and MMP-2 expression with known prognostic factors, vasculogenic mimicry(VM), the mature vasculature (von Willebrand Factor) and tumor induced angiogenesis (by means of Endoglin expression). Results CD147 and MMP-2 were expressed in 47 (96.0 %) of the uveal melanomas. CD147 up-regulation was significantly correlated with a higher MMP-2 expression. The overall expression analysis revealed no significant difference in the metastatic (p =  0.777) and non-metastatic subgroup (p =  0.585). No correlation of CD147 expression and any system of blood supply was evident. In the non-metastatic sub-group a significant correlation of clustered CD147 positive cells with largest basal diameter (p =  0.039), height (p =  0.047) and TNM-stage (p =  0.013) was evident. Conclusions These data may indicate that CD147 regulates MMP-2 expression in uveal melanoma cells.